Percepciones sobre el sentido de vida de adultos emergentes de Lima Metropolitana en proceso de duelo por la muerte de un ser querido durante la pandemia de COVID-19 - Roy Arrese, Arianna Maria (2024)
The present qualitative-phenomenological research, with an exploratory and descriptive scope, aimed to identify and describe the sources of meaning in the lives of emerging adults going through the grieving process due to the death of a loved one during the COVID-19 pandemic. It also sought to describe the factors influencing their perceptions about sense of life purpose and to analyze changes in their perceptions regarding the meaning of life. The participants were adults between 18 and 30 years old residing in Lima Metropolitana, belonging to socioeconomic sectors A and B, who were grieving the loss of a loved one during the pandemic. They were selected using a non-probabilistic convenience sampling method, and they volunteered to participate. Through thematic analysis of the data, it became evident that transcendence through positive impact on the lives of others was a highly significant source of meaning for them, along with spirituality, contact with nature, the pursuit of novel learning experiences, personal growth, and autonomy. Overall, the pandemic-induced grief prompted these individuals to contemplate the purpose of their lives, either leading to increased clarity or a sense of uncertainty. Finally, the pandemic had a negative impact on the grieving process, but the changes and health-related restrictions also allowed young adults to focus more on experiencing their grief process, contributing to a healthier coping mechanism, finding meaning in loss, and reconfiguring their sources of life purpose.